Karakteristik Pendidikan Agama dan Pendidikan Keagamaan - M. Saekan Muchith (STAI ALHIKMAH Jakarta, 2015)
Abstract Target or goal that has to be produced by learning and educational process in institution of religion and religious education is completely complicated and has various meaning which have to be understood by teachers and institutional management. This complexity is multi-interactive, while subjects of knowledge learned in institution of non-religion and non-religious education are mono-interactive. The subjects of knowledge learned by those two kinds of institution are not enough by only including subjects exist in the knowledge itself, but the subjects have to be strenghtened by subjects beyond the learned knowledge. Academic and methodological complexity has implication on professionalism profile owned by teachers who are on duties in institution of religion and religious education compared to teachers who are on duties beyond those institution. Alumni who graduate from institution in religion and religious education also have different ability compared to alumni who graduate from institution of general education. Based on this assumption, every single teachers and management staffs for institution of religion and religious education have to realize and understand completely about some significant differencies in their own institution compared to general education. Keywords: Characteristics of Science, Religion and Religious Education Abstrak Target atau tujuan yang harus dihasilkan oleh proses pembelajaran dan pendidikan di lembaga pendidikan agama dan pendidikan keagamaan sangat rumit dan menyimpan berbagai makna yang harus dipahami oleh guru dan pengelola lembaga pendidikan agama dan keagamaan. Kerumitan tersebut bersifat multi-interaktif, sementara materi ilmu yang diajarkan di non lembaga pendidikan agama dan pendidkan keagamaan cukup bersifat mono-interaktif. Materi ilmu yang diajarkan di lembaga pendidikan agama dan keagamaan tidak cukup hanya meliputi materi yang ada di dalam ilmu itu sendiri, melainkan harus juga dikuatkan dengan materi di luar ilmu yang dipelajari. Kerumitan secara akademik dan metodologis berimplikasi kepada profil profesionalisme yang dimiliki oleh guru yang bertugas di lembaga pendidikan agama dan pendidikan keagamaan dengan guru yang bertugas di luarnya. Lulusan atau alumni dari lembaga pendidikan agama dan pendidikan keagamaan juga memiliki ketrampilan yang berbeda dengan alumni dari lembaga pendidikan umum. Berdasarkan pada asumsi tersebut, maka seluruh tenaga kependidikan dan pengelola lembaga pendidikan agama dan keagamaan harus memiliki kesadaran dan pemahaman yang utuh tentang perbedaan yang cukup signifikan yang ada di dalamnya dengan pendidikan umum. Kata Kunci: Karakteristik Ilmu, Pendidikan Agama, Pendidikan Keagamaan